WORKSHOP ON VILLAGE FINANCIAL MANAGEMENT AND MSME DEVELOPMENT IN CINTARATU VILLAGE - Sugiharti, Dewi Kania; Sueb, Memed; Irawadi, Cahya; Yuliafitri, Indri; Ramdhani, Rully Herdita (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Proper management of village finances is very important for the sustainability of a village and the welfare of its people. The community can participate fairly in seeking welfare by forming MSMEs to help the village economy. Knowledge about the business being managed is one of the important factors for the sustainability of the business to survive and develop it. In running MSMEs, the people of Cintaratu Village, Parigi District, and Pangandaran Regency still need to improve MSME management strategies. This is intended so that MSMEs run by the people of Cintaratu Village can further develop and can become one of the leading MSMEs in the region. Therefore, this Integrative KKN-PPM activity is expected to increase the knowledge of the Cintaratu Village community about how to develop MSMEs and the right strategy for developing them. This event was held in the form of a talk show by including a presentation containing strategies for running MSMEs, and there were also examples of content creation on TikTok. In addition, an explanation of tips on creating such content was given so that the people of Cintaratu Village could create similar content by utilizing their creativity. Through this event, the people of Cintaratu Village got a solution so they could get funding assistance, as well as knowledge on how to do digital marketing with the Tiktok platform.